The Effect of Capital Structure and Company Size on Earnings Growth in Food and Beverage Companies Listed on the Indonesia Stock Exchange (IDX) - Khairunnisa, Namirah; Nurfadillah, Mursidah; Saputra, Praja Hadi (Neraca Keuangan : Jurnal Ilmiah Akuntansi dan Keuangan, 2025)
This consider points to analyze the impact of capital structure and company measure on benefit development in nourishment and refreshment segment companies recorded on the Indonesia Stock Trade (IDX) for the 2019-2023 period. The strategy utilized could be a quantitative approach with different straight relapse examination strategies. The inquire about test comprised of 25 companies chosen through purposive testing. The comes about appeared that both somewhat and at the same time, capital structure and company estimate had no noteworthy impact on profit development. This finding demonstrates that profit development is more affected by other components exterior the factors examined.